Optimizacije v inženirstvu: Reševanje problemov z metahevrističnimi metodami v okolju MATLAB - Gotlih, Janez; Ficko, Mirko (University of Maribor Press, 2025)
Optimization in Engineering: Solving Problems with Metaheuristic Methods in MATLAB. The book covers basic optimization approaches in engineering, focusing on the use of metaheuristic methods such as genetic algorithms (GA) and particle swarm optimization (PSO). They are intended for students and engineers who want to understand both the theoretical background and the practical implementation of optimization algorithms in the MATLAB environment. They include chapters on singleobjective and multiobjective optimization problems, discuss constraints, various objective functions, and visualization of results. Each chapter contains structured exercises and assignments for independent work that promote understanding of how algorithms work, the design of optimization models, and the interpretation of solutions. Special emphasis is placed on explaining algorithm parameters, comparing c onvergence, and the impact of settings on optimization behavior. The book concludes with an overview of typical test functions and examples of Pareto fronts for multi-objective optimization. It is designed so that even users without in-depth mathematical knowledge can gradually develop an intuition for using optimization approaches in real engineering problems.